Incidencia de los usos de suelo en la calidad de vida de los habitantes de la microcuenca del río carrizal - Rodríguez Bravo, Renata Alejandra (2017)
The investigation (research) had as aim (lens) evaluate the incident of the uses of soil in the quality of life of the inhabitants of the microbasin of the Rio Carrizal. By means of methods and technologies (skills) like observation, surveys, images satelitales and georreferenciación. The obtained results demonstrated that the use of soil of these communities has changed during the last years as consequence of the construction of the Dam the Hope, existing a decrease of forest forests, expansion of the agricultural(farming) border, influencing the use of the soil, coming this way to 64.04 % of the area destined for the agriculture, 38.01% of the land for agriculture and raising(castle) and 34.21% in forests, complemented the agricultural wealth of the place in a 26.32%, since the people taking advantage of the agro-climatic conditions have chosen producing crops, occupying 54.39 % for short and everlasting cultures(culturing) in sectors as Julián and Balsa en Medio, and 41.52 % to short cultures(culturing) in Severino's community; so much 63.45 % of the crop is destined to the self-consumption and 29.83 % between(among) commercialization